A New 4-D Chaotic System with Hidden Attractor and its Circuit Implementation - Sambas, Aceng; Mamat, Mustafa; Vaidyanathan, Sundarapandian; Mohamed, Muhammad; Sanjaya, Mada (International Journal of Engineering and Technology, 2018)
In the chaos literature, there is currently significant interest in the discovery of new chaotic systems with hidden chaotic attractors. A new 4-D chaotic system with only two quadratic nonlinearities is investigated in this work. First, we derive a no-equilibrium chaotic system and show that the new chaotic system exhibits hidden attractor. Properties of the new chaotic system are analyzed by means of phase portraits, Lyapunov chaos exponents, and Kaplan-Yorke dimension. Then an electronic circuit realization is shown to validate the chaotic behavior of the new 4-D chaotic system. Finally, the physical circuit experimental results of the 4-D chaotic system show agreement with numerical simulations.